Teachers' Strategies in Understanding Student Learning Styles in Indonesian Learning for Grade IV.A Students at SDN 2 Jenggala for the 2023/2024 Academic Year - LISTIANI; Hadi, Rusman; Sukarto (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
Abstract Listiani (2024), this study aims to determine teachers' strategies in understanding students' learning styles in Indonesian learning for grade IVA students at SDN 2 Jenggala, Tanjung District. This type of research is a descriptive qualitative research, the data collection techniques used in this study are observation, interviews, and documentation. The information collected came from the principal, classroom teachers, and students at SDN 2 Jenggala. The data analysis techniques used in this study are through several stages, including 1) Restrictions on research studies. 2) develop questions. 3) planning the stages of data collection and paying attention to the results of previous observations. 4) re-check the collected data. 5) Systematically arranging the records of observation and interview results. 6) Describe and describe all data, namely observations and interviews.The results of this study are that the learning style used by grade 4A students is visual and auditory learning style, the strategy used by the teacher is the expository learning strategy, for the visual learning style is by using pictures and videos while visual, namely students prefer to discuss and listen to the teacher's explanation on the board, the positive impact is that students are more enthusiastic and easier to understand the subject matter, the negative impact is less time when explaining the learning material.